Design and Development of Optimum Power Output for Tidal Energy System Application - Noor Hidayah M. Yunus (2013)
The paper discusses on developing optimum powers for tidal energy system application. The optimum power will be produce from the Direct Current (DC) to DC converter by the power electronics application system. To get the maximum power DC to DC buck-boost chopper that will step up or step down voltage depending on voltage input. In terms of the mechanical solution part, a research on which design of blade or rotor are the best selection to obtain the maximum power and concerning other mechanical design can be implemented to the system to obtain optimum output voltage. The system will be attached between mechanical part (generator) and DC to Alternating Current (AC) converter (Inverter) to control the power output from the tidal turbine. The power from the tidal generator will be converting to DC supply before the maximum power circuit control attached in the system. The output voltage from the maximum power circuit control will be converting to the AC power by using the inverter application. The last part of the system before distribute to the user is AC voltage transformer to step-up the voltage. The power output from the tidal energy system will be always maximum value either the lower or higher sea current.